If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2xy + 3yz = -5xz + -2xy Reorder the terms: 2xy + 3yz = -2xy + -5xz Solving 2xy + 3yz = -2xy + -5xz Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2xy' to each side of the equation. 2xy + 2xy + 3yz = -2xy + 2xy + -5xz Combine like terms: 2xy + 2xy = 4xy 4xy + 3yz = -2xy + 2xy + -5xz Combine like terms: -2xy + 2xy = 0 4xy + 3yz = 0 + -5xz 4xy + 3yz = -5xz Add '5xz' to each side of the equation. 4xy + 5xz + 3yz = -5xz + 5xz Combine like terms: -5xz + 5xz = 0 4xy + 5xz + 3yz = 0 Add '-3yz' to each side of the equation. 4xy + 5xz + 3yz + -3yz = 0 + -3yz Combine like terms: 3yz + -3yz = 0 4xy + 5xz + 0 = 0 + -3yz 4xy + 5xz = 0 + -3yz Remove the zero: 4xy + 5xz = -3yz Combine like terms: -3yz + 3yz = 0 4xy + 5xz + 3yz = 0 The solution to this equation could not be determined.
| 4z-9z+2=0 | | -(8y+1)-(-7y-5)=5 | | x=-5x^2+6x+9 | | y(x)=-16x^2+64x | | a=2a+(-3) | | 500t=1000/300 | | x=-5x^2+8x+9 | | x^3+x^2+3*x+5=0 | | 2x-(5a+7x)=8x+(-3x+7a)-2a | | 3=j+2 | | f(x)=-5x^2+8x+9 | | 15(m+5)-3(8m+7)= | | 125x^2=12 | | -x^2-6x-8= | | -1=-5+I | | 6+2r-3=6r+3-3r | | 3[7x-2(y-1)]= | | 2=H-4 | | 2=H+4 | | u-1/8 | | -3x^2-6x-8= | | m^2-2*m+2=0 | | 4(x-2)-6(9x+7)= | | z^2-11z+19=-5 | | u-2/4 | | 9x+4x=78 | | x^2-2*m+2=0 | | -3=14+g | | y/4=-30 | | 2x^2-62x-140=0 | | I=-20x^2+400x | | -4=6(t-4)-5t |